Alteration of reactive oxygen species master transcription factor Nrf2 in keratinocytes exposed to monoclonal pathogenic antibody AK23 against desmoglein-3 in pemphigus vulgaris - Faris Mohsin Ali Alabeedi (Taylor & Francis Group, 2024)
Keratinocytes in mucosal and skin tissues maintain tissue integrity via desmosomes and desmoglein-3 (Dsg3). Pemphigus Vulgaris (PV) is a life-threatening autoimmune blistering disease characterized by autoantibodies against Dsg3, disrupting desmosomes. Nuclear factor erythroid 2-related factor 2 (Nrf2) regulates oxidative stress responses crucial for skin tissue protection. Although the pathogenesis of PV is known, the detailed molecular events remain unclear. This study investigates changes in Nrf2 expression in keratinocytes following pathogenic anti-Dsg3 antibody AK23 exposure, using dose- and time-dependent studies employing immunofluorescence analysis. N/TERT keratinocytes were cultured in keratinocytes serum-free medium and treated with AK23 at varying doses (5 µg/mL,40µg/mL,75µg/mL) and durations (2, 6, 24 h). Immunofluorescence staining was performed to assess the expression of Nrf2 and Dsg3. All fluorescent images were analyzed using ImageJ software. A dose-dependent increase in Dsg3 was noted following AK23 treatment, while Nrf2 expression and subcellular localization varied. Time-course analyses showed decreased Nrf2 at 24 h and increased Dsg3 levels. Early time-point (2 and 6 h) variations were evident in Nrf2 levels. This study highlights the impact of AK23 on Nrf2 expression, potentially disrupting Nrf2-mediated cytoprotection and implicating oxidative stress (ROS generation) in PV pathogenesis. Further investigation is necessary to validate the findings.